PERAN BADAN PENGAWAS PEMILU DALAM UPAYA PENCEGAHAN DAN PENYELESAIAN SENGKETA HASIL PEMILU DI MAHKAMAH KONSTITUSI - Syaiful Bachri (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2022)
The 2019 General Election is an important event in the history of democracy, the design of the simultaneous election in which there are 5 (five) elections including the Presidential and Vice-Presidential Election, the Election of Members of the People's Representative Council (DPR), Members of the Regional Representatives Council (DPD), Members of the Regional People's Representative Council Province (Provincial DPRD) and Members of Regency/City Regional People's Representative Council (Regency/City DPRD). Disputes over election results are closely related to the process of voting and counting and recapitulation of vote counting because the output is the result of votes, Bawaslu as the party giving information at the Court session Constitution on several cases of dispute over election results as an effort and role of Bawaslu as election supervisor which conveys the results of supervision, handling of violations, both as stated in the main arguments of the petition and outside the main petition, as one of the considerations of the judges of the Constitutional Court in deciding dispute cases. the election results. The construction of Bawaslu's authority as a supervisory agency in it is related to the resolution of election disputes and is an integral part in handling violations. In this case, Bawaslu's prevention efforts (preventiom of electoral disputes) can accommodate election participants in conveying their dissatisfaction and interests with the election organizers, in this case the General Election Commission.